2022
DOI: 10.1002/brb3.2476
|View full text |Cite
|
Sign up to set email alerts
|

Variability of EEG electrode positions and their underlying brain regions: visualizing gel artifacts from a simultaneous EEG‐fMRI dataset

Abstract: Introduction:We investigated the between-subject variability of EEG (electroencephalography) electrode placement from a simultaneously recorded EEG-fMRI (functional magnetic resonance imaging) dataset.Methods: Neuro-navigation software was used to localize electrode positions, made possible by the gel artifacts present in the structural magnetic resonance images. To assess variation in the brain regions directly underneath electrodes we used MNI coordinates, their associated Brodmann areas, and labels from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 48 publications
1
70
0
Order By: Relevance
“…Smaller electrodes lead to more focal electric fields in the brain ( Mikkonen et al, 2020 ). Together with the standardized electrode locations we used, it could thus be that the peak electric fields were not located at the intended M1 target due to interindividual differences in brain anatomy relative to standardized EEG locations ( Scrivener and Reader, 2022 ). Nonetheless, modeling studies indicate that the small stimulation electrodes generate electric fields in M1 that exceed those of large electrodes (up to 35 cm 2 ) in a broad cortical area ( Mikkonen et al, 2020 ), supporting the use of small electrodes in standardized EEG locations.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller electrodes lead to more focal electric fields in the brain ( Mikkonen et al, 2020 ). Together with the standardized electrode locations we used, it could thus be that the peak electric fields were not located at the intended M1 target due to interindividual differences in brain anatomy relative to standardized EEG locations ( Scrivener and Reader, 2022 ). Nonetheless, modeling studies indicate that the small stimulation electrodes generate electric fields in M1 that exceed those of large electrodes (up to 35 cm 2 ) in a broad cortical area ( Mikkonen et al, 2020 ), supporting the use of small electrodes in standardized EEG locations.…”
Section: Discussionmentioning
confidence: 99%
“…Here, occlusion sensitivity explained that neural activity from the central and left frontal region made the most important contribution to speech understanding. The topographic map of occlusion sensitivity in PH and PHENV cases showed that the language dominant region (typically F3 within the middle frontal gyrus and TP7 within the middle temporal gyrus) was highly involved in speech intelligibility processes ( Scrivener and Reader, 2022 ). The results are comparable with the findings of neuroimaging studies, specifically that of the sentence-processing network, including the middle frontal and middle temporal gyri ( Peelle et al, 2004 , 2010 ; Fiebach et al, 2005 ; Smirnov et al, 2014 ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Artifacts greatly influence the data obtained from simultaneous EEG-fMRI ( Scrivener and Reader, 2022 ). On one hand, wearing the helmet causes a variation in the magnetic field’s homogeneity, resulting in a variation in image quality; on the other hand, the magnetic field itself causes broad-band artifacts that almost entirely cover the electroencephalographic signal ( Steyrl and Müller-Putz, 2019 ).…”
Section: Simultaneous and Non-simultaneous Functional Magnetic Resona...mentioning
confidence: 99%